Environmental worldviews and attitudes of public-sector urban planners in shaping sustainable urban development: the case of South Africa - Read, Rebecca; Shackleton, Charlie M.; Sinasson Sanni, Gisele K. (Frontiers in Sustainable Cities, 2024)
Public-sector urban planners are essential role-players in the development of sustainable cities.However, there is relatively little understanding of their perceptions of sustainability generally and how or where they obtain information and knowledge around urban sustainability, especially in the Global South. This study, therefore, adopted a mixed-methods approach, employing both an online survey (34 valid respondents) and eight in-depth interviews (together spanning 31 different municipalities), to assess the knowledge, attitudes, and worldviews (based on the New Ecological Paradigm scale) of public-sector planners in South Africa. Generally, the planners held ecocentric worldviews and acknowledged the importance of sustainable urban development and the need to understand urban ecological dynamics and principles in planning and urban greening. However, they also identified a range of factors that hinder their ability to plan for sustainable futures, including institutional flaws, politics and misaligned development goals. Most felt that the extent and distribution of urban green infrastructure in their municipality was below what they deemed as ideal, although the majority were unaware of national guidelines in this respect. Consequently, perceptions and worldviews appeared to be misaligned with what is prioritised and implemented. Therefore, environmental issues and ecological principles need to be better communicated to public-sector urban planners.